Out of the box thinking: challenges and future perspectives for food-grade nutraceutical delivery systems - Yafei Zhang; Yiran Wang; Kai Zhang; Xiaoya Lin; Yi Xue; Zhengyang Zhang (Food Materials Research)
Food-grade nutraceuticals often have unstable properties and are easily decomposed under the influence of light, heat, pH, and other conditions during processing and digestion. Moreover, many hydrophobic nutraceuticals are characterized by poor solubility, low bioaccessibility, and low bioavailability, which limits the widespread utilization of food-grade nutraceuticals. With the development of food-grade nutraceutical delivery system technology (FNDS), the utilization barrier of food-grade nutraceuticals has been gradually overcome, so that food-grade nutraceuticals are increasing in their effective used. However, the development of FNDS still faces many challenges. Herein, the safety of FNDS is first discussed. In addition, the stability of FNDS in different environments remains to be improved. Besides, the FNDS also has the challenge of off-target effect. In the future, the development direction of FNDS might be exploring the multi-nutrient co-delivery system, designing new types of FNDS, and clarifying the nutraceuticals release mechanism, and their final fate. The challenges and future perspectives of FNDS have been considered critically and summarized in this review, to promote the development of FNDS and the wide application of nutraceuticals.